Electrochemically shape-controlled synthesis of great stellated dodecahedral Au nanocrystals with high-index facets for nitrogen reduction to ammonia. Issue 81 (10th September 2020) - Jiang, Yu-Chen; Mao, Yu-Jie; Zou, Jin; Wang, Hong-Hui; Liu, Feng; Wei, Yong-Sheng; Sheng, Tian; Zhao, Xin-Sheng; Wei, Lu
Abstract : High-index {331} faceted Au great stellated dodecahedra are synthesized by a double-step potential method in an ageing HAuCl4 /DES solution, which exhibit excellent electrocatalytic activity for the nitrogen reduction reaction. Abstract : Au great stellated dodecahedra (GSD), one of the Kepler–Poinsot solids, are synthesized by an electrochemical double-step potential method in a choline chloride-urea based deep eutectic solvent. The as-synthesized Au GSD are bound by high-index {331} facets and exhibit excellent electrocatalytic performance for the nitrogen reduction reaction with a high NH3 yield rate (49.96 μg h −1 cm −2 ) and faradaic efficiency (28.59%) under ambient conditions.